Cancer risk after radiotherapy for benign diseases. (October 2017) - Mazonakis, M.; Damilakis, J.
Highlights: Cancer risk estimates from radiotherapy for benign disorders is of clinical value. The use of epidemiologic data from studies of cohorts can provide reliable cancer risk estimates. Organ-specific cancer risk estimates are useful to weigh the risks and benefits of radiotherapy. Abstract: Radiotherapy with low to intermediate doses has been historically employed for the management of several benign diseases. The exposure to ionizing radiation may increase the probability for carcinogenesis. The knowledge of this probability is of value for weighting the benefits and risks of radiotherapy against different therapeutic approaches. This study initially reviews the epidemiologic data associated with the cancer induction due to radiotherapy for non-malignant conditions in previous decades. Most of these data were derived from patients irradiated with conventional techniques, which are no longer applied, for some benign diseases not treated with radiotherapy nowadays. The follow-up of a series of patients undergoing modern radiotherapy for benign disorders may be used for estimating the radiation-induced cancer risk. The realization of this process is often difficult due to the relatively small number of patients undergoing radiation therapy for such diseases in many countries and due to long latent period for the appearance of a malignancy after exposure. The combination of dosimetric data, which can be obtained by phantom measurements or treatment planning systems or Monte Carlo calculations, with the appropriate linear and non-linear risk models may lead to theoretical estimates of the radiotherapy-induced cancer risks. The limitations of the method providing a whole-body cancer risk based on the effective dose concept are presented. The theoretical organ-specific risks for carcinogenesis give useful information about the development of malignancies at any in-field, partially in-field and out-of-field critical site. The uncertainties of the organ-dependent cancer risk estimates are discussed.